2022
DOI: 10.3168/jds.2022-21934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding rumen-protected lysine through the transition period on postpartum uterine health of dairy cows

Abstract: Feeding rumen-protected methionine as an indispensable amino acid source has been shown to improve reproductive performance in dairy cows, but the effect of feeding rumen-protected lysine (RPL) during the peripartum period on reproductive performance is not well explored. Therefore, we aimed to determine the effects of feeding RPL (AjiPro-L Generation 3, Ajinomoto Heartland Inc.) prepartum, postpartum, or both on follicular dynamics, uterine health, and mRNA gene expression of the endometrium. Seventy-five mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…In a previous study involving RPL supplementation during the pre‐ and/or post‐partum periods, uterine tissue transcripts linked to inflammation were downregulated 28 days postpartum in cows receiving prepartum RPL supplementation; yet, the PMN percentage was unaffected (Guadagnin et al., 2022). Uterine microbiota similarity was observed between subclinical endometritis and healthy cows at 35 days postpartum; yet, clinical endometritis cows had distinct microbiomes with relatively low bacterial diversity (Pascottini et al., 2020).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a previous study involving RPL supplementation during the pre‐ and/or post‐partum periods, uterine tissue transcripts linked to inflammation were downregulated 28 days postpartum in cows receiving prepartum RPL supplementation; yet, the PMN percentage was unaffected (Guadagnin et al., 2022). Uterine microbiota similarity was observed between subclinical endometritis and healthy cows at 35 days postpartum; yet, clinical endometritis cows had distinct microbiomes with relatively low bacterial diversity (Pascottini et al., 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Guadagnin et al. (2022) demonstrated that peripartum RPL supplementation did not affect the postpartum follicular dynamics or first ovulation. In that study, the first ovulation occurred 18 days after parturition; most experimental cows ovulated at the time of the earliest ovulation after parturition, and reproductive physiology made it impossible to ovulate earlier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multiple regression analysis indicated that milk production and milk protein percent were significantly higher when RPM was fed [47]. Amino acids have also been reported to have benefits for reproduction, transition cow health and heat stress [48][49][50][51].…”
Section: Nitrogen and Ammoniamentioning
confidence: 99%